Representasi Kritik Sosial dalam Karikatur Serangan IDF Terhadap Rumah Sakit As-Syifa Palestina - An Shori, Alam; Hasanah, Ummi; Jambak, Melinda Raswari; Wargadinata, Wildana (Jurnal Media dan Komunikasi Indonesia, 2024)
The IDF (Israel Defense Forces) raid on As-Shifa hospital is a serious problem as it is related to international humanitarian rules regarding civilian objects. Emad Hajjaj on his Instagram account criticized this behavior with caricatures. This study aims to (1) uncover the representation of social criticism in Emad Hajjaj's caricature on Instagram and (2) uncover the factors behind caricature making. The primary data source comes from two caricatures on Emad Hajjaj's Instagram account, while the secondary data comes from books, journals, news, and articles relevant to this study. This type of research is qualitative research using the semiotic approach of Roman Jakobson's perspective and Gillin and Gillin's theory of social criticism. The data collection techniques used are screenshots, reading, and notes. Data analysis techniques use the Miles and Huberman technique which consists of data reduction, data presentation, and conclusions. The result of this study is that there are two types of representations of social criticism in Emad Hajjaj's caricature related to the attack on IDF soldiers, namely socio-political criticism and social moral criticism. The background to the criticism was a response to the actions of IDF soldiers.